2021
DOI: 10.1039/d1nj04188f
|View full text |Cite
|
Sign up to set email alerts
|

C5H2N14O6: achieving azido-based materials with zero oxygen balance and good energetic performance

Abstract: In this study, an azido-based compound 4, N,N'-methylenebis(N-(4-azido-1,2,5-oxadiazol-3-yl)nitramide), was synthesized and fully characterized. The crystal structure of 4 was determined for the first time to investigated the structure-performance relationship. Material...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…9 As shown in Fig. 1b, 10 we found that the nitro group has more active influence on density than the azide group. In a previous work, our group reported the synthesis of 4-azide-5-dinitromethyl-1,2,3-triazole and its energetic salts, which show good detonation performance, but low density.…”
Section: Introductionmentioning
confidence: 52%
“…9 As shown in Fig. 1b, 10 we found that the nitro group has more active influence on density than the azide group. In a previous work, our group reported the synthesis of 4-azide-5-dinitromethyl-1,2,3-triazole and its energetic salts, which show good detonation performance, but low density.…”
Section: Introductionmentioning
confidence: 52%
“…Azido is an energetic group with high positive HOF and has been introduced into different azole rings to synthesize new energetic compounds . A dinitromethyl group has been wildly used in the design and synthesis of new energetic compounds and is believed to be a good energetic group for improving the oxygen balance and density of energetic compounds, thus leading to better detonation performances .…”
Section: Introductionmentioning
confidence: 99%
“…A dinitromethyl group has been wildly used in the design and synthesis of new energetic compounds and is believed to be a good energetic group for improving the oxygen balance and density of energetic compounds, thus leading to better detonation performances . While the introduction of the azide group will extremely increase the nitrogen content and the HOF of the corresponding energetic compound and is also helpful for improving the detonation performances of energetic compounds . In the current study, we tailored the properties of 1,2,3-triazole by introducing azide and dinitromethyl groups and successfully prepared a series of new 1,2,3-triazole-based energetic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lack of oxygen content in tetrazole derivatives limits their detonation performance and practical applicability in comparison to nitro-or nitroaminobased compounds. [23][24][25][26][27] Replacing the tetrazole ring with 1Htetrazol-1-ol is known to enhance the density, oxygen balance, thermal stability, insensitivity, and detonation power. 28 Notable examples include, 5,5 0 -bistetrazole-1,1 0 -diol (1,1-BTO) and dihydroxylammonium 5,5 0 -bistetrazole-1,1 0 -diolate (TKX-50) as high-performing high-energy-density materials (HEDMs) (Fig.…”
Section: Introductionmentioning
confidence: 99%